Association Between AMH Levels and Fertility/Reproductive Outcomes Among Women Undergoing IVF: A Retrospective Study - AS Vijay; MM Reddy Gopireddy; S Fyzullah; G Priyanka; M M; U Rani; S Rajesh (JRI, 2022)
Background: Anti-mullerian hormone (AMH) is a marker for predicting ovarian response to gonadotropin stimulation. It plays an important role in ovarian primordial follicle recruitment and dominant follicle selection. Therefore, the present study evaluated the AMH levels and their association with fertility/reproductive outcomes among women undergoing IVF. Methods: A retrospective study was conducted on 665 women in GarbhaGudi Institute of Reproductive Health and Research in India from October 2018 to 2019. Subjects were divided into ≥1.1 and ≤1.1 AMH level groups. Data on age, luteinizing hormone; LH (mIU/L), follicle-stimulating hormone values; FSH (mIU/ml), LH value, oocytes retrieved, and oocytes fertilization were collected. AMH category was considered as the primary explanatory variable. Independent sample t-test and chisquare tests were performed. The p<0.05 was considered statistically significant. Results: Couple’s age, FSH values (mIU/ml), number of large follicles, matured oocytes, fertilized oocytes, and cleaved embryos were statistically significant (p<0.001) among subjects with ≥1.1 AMH values. Percentage of women with successful embryo transfer was slightly higher among AMH category 1.1 (p=0.09). Fertilization rate (86.67±20.08 vs. 83.64±21.39, p=0.18) and clinical pregnancy rate (43.38% vs. 36.36%, p=0.19) were slightly higher among women with AMH level of ≥1.1 as compared to AMH of <1.1. Live birth rate was slightly higher among women with AMH level of 1.1 (25.85% vs. 22.22%, p=0.45). Also, the number of fertilized oocytes was associated with clinical pregnancy rate (aOR=1.20, 95%CI 1.09-1.33). Conclusion: Women with ≥1.10 serum AMH levels had more number of retrieved oocytes, good oocyte quality, increased embryo transfer, and fertilization rates.